Evolving changes in cortical and subcortical excitability during movement preparation: A study of brain potentials and eye-blink reflexes during loud acoustic stimulation - Nguyen, An; Tresilian, J.R.; Lipp, Ottmar; Tavora-Vieira, D.; Marinovic, Welber (WILEY, 2023)
During preparation for action, the presentation of loud acoustic stimuli (LAS) can trigger movements at very short latencies in a phenomenon called the StartReact effect. It was initially proposed that a special, separate subcortical mechanism that bypasses slower cortical areas could be involved. We sought to examine the evidence for a separate mechanism against the alternative that responses to LAS can be explained by a combination of stimulus intensity effects and preparatory states. To investigate whether cortically mediated preparatory processes are involved in mediating reactions to LAS, we used an auditory reaction task where we manipulated the preparation level within each trial by altering the conditional probability of the imperative stimulus. We contrasted responses to non-intense tones and LAS and examined whether cortical activation and subcortical excitability and motor responses were influenced by preparation levels. Increases in preparation levels were marked by gradual reductions in reaction time (RT) coupled with increases in cortical activation and subcortical excitability – at both condition and trial levels. Interestingly, changes in cortical activation influenced motor and auditory but not visual areas – highlighting the widespread yet selective nature of preparation. RTs were shorter to LAS than tones, but the overall pattern of preparation level effects was the same for both stimuli. Collectively, the results demonstrate that LAS responses are indeed shaped by cortically mediated preparatory processes. The concurrent changes observed in brain and behavior with increasing preparation reinforce the notion that preparation is marked by evolving brain states which shape the motor system for action.